Chiral Multi‐Resonance TADF Emitters Exhibiting Narrowband Circularly Polarized Electroluminescence with an EQE of 37.2 %. (8th June 2022) - Yang, Yiyu; Li, Nengquan; Miao, Jingsheng; Cao, Xiaosong; Ying, Ao; Pan, Ke; Lv, Xialei; Ni, Fan; Huang, Zhongyan; Gong, Shaolong; Yang, Chuluo
Abstract: Highly efficient circularly polarized luminescence (CPL) emitters with narrowband emission remain a formidable challenge for circularly polarized OLEDs (CP‐OLEDs). Here, a promising strategy for developing chiral emitters concurrently featuring multi‐resonance thermally activated delayed fluorescence (MR‐TADF) and circularly polarized electroluminescence (CPEL) is demonstrated by the integration of molecular rigidity, central chirality and MR effect. A pair of chiral green emitters denoted as ( R )‐BN‐MeIAc and ( S )‐BN‐MeIAc is designed. Benefited by the rigid and quasi‐planar MR‐framework, the enantiomers not only display mirror‐image CPL spectra, but also exhibit TADF properties with a high photoluminescence quantum yield of 96 %, a narrow FWHM of 30 nm, and a high horizontal dipole orientation of 90 % in the doped film. Consequently, the enantiomer‐based CP‐OLEDs achieved excellent external quantum efficiencies of 37.2 % with very low efficiency roll‐off, representing the highest device efficiency of all the reported CP‐OLEDs. Abstract : The combination of central chirality and multi‐resonance framework derives a set of chiral enantiomers concurrently featuring narrowband emission and circularly polarized (CP) thermally activated delayed fluorescence. Owing to high rigidity and quasi‐planarity of the skeleton, a high photoluminescence quantum yield of 96 %, a FWHM of 30 nm, as well as a high horizontal dipole orientation of 90 % are acquired in the doped film. Corresponding CP‐OLEDs manifest a record‐high external quantum efficiency up to 37.2 % with low efficiency roll‐off, and obvious circularly polarized electroluminescence.